Fatigue in Hemodialysis Patients: A Comparative Analysis with Healthy Controls - Leszek Sułkowski; Andrzej Matyja; Maciej Matyja (European Journal of Investigation in Health, Psychology and Education)
This study investigates fatigue and quality of life in hemodialysis patients, examining the influence of demographic and clinical factors on these outcomes. A cohort of 115 hemodialysis patients and 112 healthy controls completed the Modified Fatigue Impact Scale (MFIS), the shorter MFIS-5, and the WHOQOL-BREF quality of life assessment. The findings indicate that hemodialysis patients experience significantly higher levels of fatigue, which correspond with lower quality of life, particularly in the physical and psychological domains, compared to healthy controls. Male patients reported significantly higher levels of fatigue and lower quality of life scores, whereas younger patients demonstrated relatively better outcomes. Extended dialysis sessions exceeding four hours were associated with poorer social well-being, and educational attainment was positively linked with physical and environmental quality of life domains. However, marital status did not show a significant effect. The study validates the consistency between MFIS and MFIS-5 scores, recommending MFIS-5 for time-sensitive clinical use without compromising accuracy. These results underscore the need for individualized, multi-dimensional approaches to fatigue management in hemodialysis patients, emphasizing interventions that address physical, psychological, and social well-being to enhance overall quality of life. The findings highlight specific factors that may guide tailored support strategies to improve patient outcomes in this population.